Perception, attitude and practice towards melioidosis among older adults in Kota Bharu: development, validation and cross-sectional study - Muthusamy, Vinoth Viknesh (2020)
Melioidosis is an emerging infectious disease that is endemic toward the northeast of Kelantan in Malaysia. The muddy clay rich soils in Kota Bharu and heavy rainfall during the monsoon season of November to March every year serve as breeding ground for a dangerous disease that is relatively unknown. It is especially vicious toward older people who are more susceptible to its infection and possible complication. This is compounded by the lack of proper perception, attitude and practice towards managing the disease among older adults. This study aims to develop and validate a questionnaire which can measure perception, attitude and practice regarding Melioidosis among older adults in Kota Bharu, following which to determine perception, attitude and practice regarding Melioidosis among them in Kota Bharu and to determine the factors associated to perception, attitude and practice regarding Melioidosis in Kota Bharu. This was a dual design study conducted in 2019 in Kota Bharu among older adults. The questionnaires were developed by an expert panel of three professionals from varying public health fields based upon pre-existing KAP questionnaires and validated through a validation study consisting of 108 older adults’ individuals using EFA using IRT for the section on perception, PCA and Oblimin rotation methods for attitude and practice and CFA using the Maximum Likelihood estimation method. The validated questionnaires were distributed among 260 older adults’ respondents in Kota Bharu. Their score in perception, attitude and practice towards melioidosis were scored using this newly developed and validated questionnaire. All the scores were compared to sociodemographic factors such as age, gender, marital stat educational level, income status, employment status and presence of co- morbid to determine associated factors for good knowledge, attitude and practice. The questionnaire was found to be valid with a good IRT scores for perception and two factor solution with a good KMOMSA for attitude and practice. It was also reliable with a Cronbach’s Alpha of 0.81, a high degree of fit with all confirmatory indices with a cumulative RMSEA of 0.18, CFI of 0.967 and TLI of 0.953. A cut off 80 percent was determined using prior literature as good scores. The surveyed respondents scored poorly on perception with 75.8% getting a poor score. The attitude scores were better, with 79.6% of the respondents getting a good score while the practice scores were mediocre with only 41.5% of the respondents getting a good score. Tertiary education was found to be associated with good scores in perception (OR 2.110; 95% CI: 1.792, 4.603 p=0.005). For good attitude scores, secondary education (OR 3.92; 95% CI:1.60, 9.57 p=0.003) and tertiary education (OR 3.329; 95% CI: 1.14, 9.72 p=0.028) were found to be significant. While for good practice, employment status (OR 1.63; 95% CI: 1.43, 2.94 p=0.040) had a significant association. The developed questionnaire was found to be valid and reliable. Older adults in Kota Bharu have a poor perception towards melioidosis together with mediocre practice. Although they have good attitude toward melioidosis due to the exposure to other similar infectious disease, all these scores seem to be significantly tied towards the educational level or employment status of the respondent. Health programs to improve the perception of the older adults in Kota Bharu, especially towards those who are not well-educated will be essential in combating the emerging infectious disease.